Optimizing Offline Mode and Data Synchronization Techniques for Literature Translation Applications on Mobile Devices - Wang, Fei; Wang, Yuanyuan (International Journal of Interactive Mobile Technologies (iJIM), 2024)
The widespread use of mobile devices has intensified the demand for literature translation in both academic research and personal learning. However, existing translation applications face significant challenges regarding offline mode and data synchronization. Ensuring translation quality and efficient data synchronization, particularly under unstable or disconnected network conditions, has emerged as a critical issue. Current research predominantly focuses on local storage and update mechanisms in offline mode. However, limitations in storage capacity and update strategies often hinder translation effectiveness. Additionally, data synchronization techniques have been primarily studied in stable network environments, with insufficient attention to strategies that address poor network quality or intermittent connectivity. To address these gaps, this study explores the offline mode and data synchronization technologies in literature translation applications on mobile devices. The study proposes optimized storage and update strategies for the offline mode while enhancing the efficiency and reliability of data synchronization, ultimately improving the usability and user experience of translation applications.